A kind of asphalt-based silicon-carbon composite material and preparation method thereof

By doping sodium bicarbonate and sodium borohydride during the preparation process of pitch-based porous carbon, and performing metal doping and secondary coating of amorphous carbon, the difficulty in controlling the pores of pitch-based porous carbon materials in the existing technology is solved. problem, achieving efficient preparation of silicon-carbon materials and improving the electronic conductivity and rate performance of the materials.

CN118693269BActive Publication Date: 2025-01-24ZHIHUA NEW ENERGY TECH (ZHEJIANG) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411163040.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2025-01-24
Estimated Expiration
2044-08-23

AI Technical Summary

Technical Problem

The pores of the asphalt-based porous carbon material obtained by the existing methods are difficult to control and have a small pore size, resulting in less deposition of nano-silicon, poor electronic conductivity, poor first-time efficiency, and difficult to use on a large scale.

Method used

By doping sodium bicarbonate and sodium boroside during the preparation of asphalt -based porous carbon, forming a porous structure and generating sodium doped porous carbon, reducing expansion and increasing electronic conductive rates. At the same time, metal doping is performed by real air -based metal compounds, and the secondary covering of passivation treatment and secondary carbon is performed to improve the magnification performance and first efficiency of the material.

Benefits of technology

The low -cost and high -strength silicon carbon material is achieved, the defects of the material are reduced, the electronic conductivity and magnification performance is improved, and the full -scale use is suitable for large -scale use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118693269B_ABST
    Figure CN118693269B_ABST
Patent Text Reader

Abstract

The present invention discloses a pitch-based silicon-carbon composite material, which presents a core-shell structure, wherein the core is metallic silicon-doped porous carbon, and the shell is a silicon dioxide layer and an amorphous carbon layer from the inside to the outside; calculated according to the mass ratio of the composite material of 100%, the mass ratio of the first shell silicon dioxide layer is 0.5-2wt%, and the mass ratio of the second shell amorphous carbon layer is 1-5wt%. The silicon-carbon composite material is prepared from asphalt-based porous carbon. By doping an activator such as sodium bicarbonate, copper chloride, and sodium borohydride in an asphalt-based porous carbon precursor, the material is pore-formed to reduce the expansion of its silicon-carbon material and increase the deposition amount of silicon to increase the specific capacity. At the same time, lithium is doped in the silicon-carbon material to reduce the defects of the material and improve the first efficiency; and by passivation treatment and amorphous carbon to restrain the expansion of silicon, the full-charge expansion of the material is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of secondary battery material preparation, and in particular to an asphalt-based silicon-carbon composite material and a preparation method thereof. Background Art

[0002] The new silicon-carbon material is used in high-energy-density lithium-ion batteries for its advantages of low full-charge expansion, high specific capacity, and first-time efficiency. The preparation method is to crack silane to generate nano-silicon and deposit it in porous carbon. The strength, pore size, and pore volume of the porous carbon determine the performance, cost, and consistency of the material. At present, the raw materials for preparing porous carbon mainly include three types: biomass-based, resin-based, and asphalt-based. During the carbonization process of biomass-based materials, uneven pore structures are easily generated between materials, resulting in poor consistency. Resin-based porous carbon has high consistency and high cost. Asphalt-based porous carbon is widely sought after by the industry for its advantages such as wide material sources, low cost, and controllable preparation process. However, the pores of asphalt-based porous carbon materials obtained by existing methods are difficult to control and have small pore sizes, resulting in a small amount of deposited nano-silicon in the material, poor electronic conductivity, and poor first-time efficiency, making it difficult to use on a large scale. Therefore, it is urgent to develop a method for preparing asphalt-based porous carbon silicon-carbon composite materials. Summary of the invention

[0003] In order to improve the rate performance and initial efficiency of silicon-carbon materials and reduce costs, the present invention provides a silicon-carbon composite material prepared using asphalt-based porous carbon as a raw material.

[0004] The first aspect of the present invention provides an asphalt-based silicon-carbon composite material, which presents a core-shell structure, wherein the core is metallic silicon-doped porous carbon, and the outer shells are silicon dioxide layers and amorphous carbon layers from the inside to the outside; calculated based on the composite material mass ratio of 100%, the mass ratio of the first outer shell silicon dioxide layer is 0.5-2%, and the mass ratio of the second outer shell amorphous carbon layer is 1-5%. The silicon-carbon composite material is prepared from asphalt-based porous carbon. During the preparation process, the asphalt-based porous carbon is doped with sodium bicarbonate and carbonized to form a porous structure to reduce expansion, and the sodium borohydride doped at the same time is carbonized to generate sodium-doped porous carbon, which reduces the defects of the material and improves the electronic conductivity of the material, thereby improving the rate performance.

[0005] A second aspect of the present invention provides a method for preparing a pitch-based silicon-carbon composite material, characterized in that it comprises the following steps:

[0006] Step S1: adding coal tar pitch, sodium bicarbonate, activator and sodium borohydride to a ball mill according to the mass ratio of coal tar pitch: sodium bicarbonate: activator: sodium borohydride = 100: 1-5: 1-5: 1-5, mixing them evenly, and transferring them to a tube furnace, first heating them to 500-600 ° C and keeping them for 1-6 h, and then heating them to 850-1150 ° C and sintering them for 1-6 h to obtain pitch-based porous carbon;

[0007] Step S2: according to the mass ratio of asphalt-based porous carbon: silane liquid: metal compound = 100-200: 100: 10-30, the asphalt-based porous carbon is transferred to the tubular furnace A, the alkyl silane liquid and the metal compound liquid are added to the reaction and mixed evenly, and the mixture is gasified at a temperature of 400-600 ° C under a vacuum degree of 0.1-1 Mpa, and then introduced into the tubular furnace A at a flow rate of 100-500 ml / min and an introduction time of 30-300 min to perform silicon and metal co-deposition to obtain a metal-doped silicon-carbon precursor material;

[0008] Step S3: The metal-doped silicon-carbon precursor material is transferred to a tube furnace, and then heated to 100-200 °C and introduced with an oxidizing mixed gas for passivation for 1-6 h, and then heated to 500-800 °C and introduced with a carbon source gas to perform vapor deposition to deposit amorphous carbon to achieve secondary coating and obtain a silicon-carbon composite material.

[0009] The activator in step S1 is selected from one or more of silver chloride, copper chloride and zinc chloride, and the activator is added mainly to enhance the pore-forming effect.

[0010] Wherein, the silane gas in step S2 is selected from one or more of dimethylsilane, diethylsilane, dichlorodiethylsilane, methyldichlorosilane, trichlorosilane, monosilane and disilane.

[0011] Wherein, the metal compound in step S2 is selected from one or more of lithium acetate, methyl lithium and butyl lithium.

[0012] The oxidizing mixed gas in step S3 is a mixed gas of one of oxygen, nitrogen dioxide, carbon monoxide, bromine and oxybromine and argon, with a volume ratio of 1-5:10 and a flow rate of 10-100 SCCM.

[0013] In step S3, the carbon source gas is selected from one or more of methane, ethane, acetylene, and ethylene, and the flow rate is 10-100 SCCM.

[0014] A third aspect of the present invention provides a negative electrode plate for a lithium ion battery, comprising a negative electrode current collector and a negative electrode material coated on at least one surface of the negative electrode current collector, wherein the negative electrode material comprises the above-mentioned silicon-carbon composite material.

[0015] A fourth aspect of the present invention provides a lithium ion battery comprising the above-mentioned negative electrode plate, which also includes a positive electrode plate and a separator between the positive electrode plate and the negative electrode plate.

[0016] Beneficial Effects of the Invention

[0017] (1) In the process of preparing asphalt-based porous carbon, the present invention doped sodium bicarbonate to form a porous structure after carbonization to reduce expansion, and simultaneously doped sodium borohydride to form sodium-doped porous carbon after carbonization. The silicon-carbon material prepared by sodium-doped asphalt-based porous carbon has the advantages of low cost and high strength, reduces material defects, improves the electronic conductivity of the material, and improves rate performance.

[0018] (2) When preparing the silicon-carbon composite material, the present invention generates gas by vacuum gasification of metal compounds and performs metal doping to obtain lithium-doped silicon-carbon material, thereby increasing the electronic conductivity of the material, improving the rate performance, and reducing the full-charge expansion of the material by restraining the expansion of silicon through passivation treatment and its amorphous carbon. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present invention provides the following drawings for illustration:

[0020] Figure 1 The SEM image of the silicon-carbon composite material prepared in Example 1 DETAILED DESCRIPTION

[0021] The asphalt-based silicon-carbon composite material and its application provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0022] Example 1

[0023] A method for preparing a pitch-based silicon-carbon composite material comprises the following steps:

[0024] Step S1: 100 g coal tar, 3 g sodium bicarbonate, 3 g silver chloride, and 3 g sodium borohydride were added to a ball mill and mixed evenly, and then transferred to a tube furnace, first heated to 550° C. and kept for 3 h, and then heated to 950° C. and sintered for 3 h to obtain asphalt-based porous carbon;

[0025] Step S2: 150 g of asphalt-based porous carbon was transferred to the tubular furnace A; 100 g of dimethylsilane liquid and 20 g of lithium acetate were added to the reactor and mixed evenly, and then gasified at a temperature of 500° C. under a vacuum degree of 0.5 MPa, and then introduced into the tubular furnace A at a flow rate of 300 ml / min for a time of 90 min to perform silicon and metal co-deposition to obtain a metal-doped silicon-carbon precursor material;

[0026] Step S3: The metal-doped silicon-carbon precursor material is transferred to a tube furnace, and then heated to 150°C and introduced with an oxygen mixed gas (volume ratio, oxygen:argon = 3:10, flow rate 50 SCCM) for passivation for 3 hours, and then heated to 700°C and introduced with ethylene gas for 3 hours for vapor deposition to deposit amorphous carbon and achieve secondary coating to obtain a silicon-carbon composite material.

[0027] Example 2

[0028] A method for preparing a pitch-based silicon-carbon composite material, characterized in that it comprises the following steps:

[0029] Step S1: 100 g coal tar, 1 g sodium bicarbonate, 1 g copper chloride, and 1 g sodium borohydride were added to a ball mill and mixed evenly, and then transferred to a tube furnace, first heated to 500° C. and kept for 6 h, and then heated to 850° C. and sintered for 6 h to obtain asphalt-based porous carbon;

[0030] Step S2: 100 g of asphalt-based porous carbon was transferred to tubular furnace A; 100 g of diethylsilane liquid and 10 g of methyl lithium were added to the reaction and mixed evenly, and the mixture was gasified at a temperature of 400° C. under a vacuum degree of 0.1 MPa, and then introduced into tubular furnace A at a flow rate of 100 ml / min for a time of 300 min to perform silicon and metal co-deposition to obtain a metal-doped silicon-carbon precursor material;

[0031] Step S3: The metal-doped silicon-carbon precursor material is transferred to a tube furnace, and then heated to 100°C and introduced with a nitrogen dioxide mixed gas (volume ratio, nitrogen dioxide: argon = 1:10, flow rate 10 SCCM) for passivation for 6 hours, and then heated to 500°C and introduced with acetylene gas for 6 hours for vapor deposition to deposit amorphous carbon and achieve secondary coating to obtain a silicon-carbon composite material.

[0032] Example 3

[0033] A method for preparing a pitch-based silicon-carbon composite material comprises the following steps:

[0034] Step S1: 100 g coal tar, 5 g sodium bicarbonate, 5 g zinc chloride, and 5 g sodium borohydride were added to a ball mill and mixed evenly, and then transferred to a tube furnace, first heated to 600° C. and kept for 1 h, and then heated to 1150° C. and sintered for 1 h to obtain asphalt-based porous carbon;

[0035] Step S2: 100 g of asphalt-based porous carbon was transferred to tubular furnace A; 100 g of dichlorodiethylsilane liquid and 30 g of butyl lithium were added to the reactor and mixed evenly, and then gasified at a vacuum degree of 1 MPa and a temperature of 600° C., and then introduced into tubular furnace A at a flow rate of 500 ml / min for 30 min to perform silicon and metal co-deposition to obtain a metal-doped silicon-carbon precursor material;

[0036] Step S3: The metal-doped silicon-carbon precursor material is transferred to a tube furnace, and then heated to 200°C and introduced into a bromine-oxygen mixed gas (volume ratio, bromine-oxygen: argon = 5:10, flow rate 100 SCCM) for passivation for 1 hour, and then heated to 800°C and introduced into methane gas for deposition for 1 hour, and vapor deposition is performed to deposit amorphous carbon to achieve secondary coating and obtain a silicon-carbon composite material.

[0037] Comparative Example 1:

[0038] The difference from Example 1 is that sodium bicarbonate, silver chloride and sodium borohydride are not added in step S1, and the rest is the same as Example 1.

[0039] Comparative Example 2:

[0040] The difference from Example 1 is that lithium acetate is not added in step S2, and the rest is the same as Example 1.

[0041] Comparative Example 3:

[0042] The difference from Example 1 is that step S3 does not perform passivation treatment, that is, no oxygen mixed gas is introduced, and the rest is the same as Example 1.

[0043] Test Case

[0044] 1. Appearance

[0045] The silicon-carbon composite material in Example 1 was subjected to SEM testing, and the test results are as follows: Figure 1 As shown. Figure 1 It can be seen that the material has a granular structure, the particle size of the material is evenly distributed, fine powder is adsorbed on the surface, and the particle size is between 3-7μm.

[0046] 2. Button battery test

[0047] The silicon-carbon composite materials in Examples 1-3 and Comparative Examples 1-3 were used as negative electrode materials for lithium-ion batteries to prepare button batteries, and the preparation method was as follows:

[0048] Add binder, conductive agent and solvent to the composite material, stir to make slurry, coat on copper foil, dry and roll to obtain negative electrode sheet; the binder used is polyvinylidene fluoride (PVDF), the conductive agent is conductive carbon black (SP), the solvent is N-methylpyrrolidone (NMP), the amount ratio of composite material, SP, PVDF and NMP is 95g:1g:4g:220mL; lithium hexafluorophosphate (LiPF 6 ) as the electrolyte, a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1 as the solvent, and the electrolyte concentration is 1 mol / L; the metal lithium sheet is the counter electrode, and the diaphragm is a polypropylene (PP) film. The button cell is assembled in an argon-filled glove box.

[0049] The electrochemical performance of button cells comprising the silicon-carbon composite materials of Examples 1-3 and Comparative Examples 1-3 was tested using a Wuhan Blue Power CT2001A battery tester with a charge and discharge voltage range of 0.005 V to 2.0 V and a charge and discharge rate of 0.1C.

[0050] The thickness D1 of the negative electrode sheet of the button cell comprising the silicon-carbon composite materials of Examples 1-3 and Comparative Examples 1-3 after rolling was tested, and then the full-charge thickness D2 of the negative electrode sheet of the button cell fully charged to 100% SOC was dissected, and then the expansion rate was calculated:

[0051] The expansion rate is =

[0052] The specific surface area and tap density of silicon-carbon composite materials were tested with reference to GB / T 38823-2020 "Silicon Carbon", and the electrical conductivity of the porous metal composite materials was tested using a four-probe tester.

[0053] The test results are shown in Table 1.

[0054] Table 1

[0055] Material First discharge specific capacity (mAh / g) First efficiency (%) <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Tap density (g / cm 3 )]]> Powder electronic conductivity (S / cm) Full charge expansion Example 1 1887.3 92.5 5.6 1.05 0.63 101.1% Example 2 1829.4 91.4 4.9 1.01 0.51 109.2% Example 3 1909.1 92.9 6.3 1.09 0.67 93.9% Comparative Example 1 1770.5 90.7 4.5 0.97 0.38 128.3% Comparative Example 2 1790.5 89.1 4.7 0.99 0.43 117.7% Comparative Example 3 1801.4 90.1 5.1 0.82 0.49 109.1%

[0056] It can be seen from the data in Table 1 that the specific capacity, first efficiency and powder conductivity of the silicon-carbon composite material prepared by the present invention are significantly better than those of the comparative example. The reason is that by doping the asphalt-based porous carbon precursor with activators such as sodium bicarbonate, silver chloride and sodium borohydride to achieve material pore formation, the expansion of the silicon-carbon material is reduced and the silicon deposition amount is increased to increase the specific capacity. At the same time, the lithium compound doped in the material reduces the defects of the material and improves the first efficiency; and through passivation treatment and amorphous carbon to restrain the expansion of silicon, the full charge expansion of the material is reduced.

[0057] 3. Soft pack battery test

[0058] The silicon-carbon composite materials of Examples 1-3 and Comparative Examples 1-3 were mixed with 90% artificial graphite as negative electrode materials to prepare negative electrode sheets. 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 ) as the positive electrode; the electrolyte is lithium hexafluorophosphate (LiPF 6 ) as electrolyte, a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (DEC) in a volume ratio of 1:1 as solvent, and an electrolyte concentration of 1.3 mol / L; Celgard 2400 membrane as separator, a 5Ah soft pack battery was prepared. The liquid absorption and retention capacity, rate and cycle performance of the negative electrode were tested respectively.

[0059] A. Liquid absorption capacity test

[0060] Use a 1mL burette and draw 1mL of electrolyte, add a drop on the surface of the electrode, and count until the electrolyte is completely absorbed, and record the time t. The test results are shown in Table 2.

[0061] B. Liquid retention rate test

[0062] According to the electrode parameters, the theoretical liquid absorption of the electrode m1 is calculated, and the weight of the electrode m2 is weighed. Then the electrode is placed in the electrolyte and soaked for 24 hours. The weight of the electrode is weighed as m3, and the liquid absorption of the electrode m3-m2 is calculated, and calculated according to the following formula: Liquid retention rate = (m3-m2) * 100% / m1. The test results are shown in Table 2.

[0063] Table 2

[0064] Material Liquid suction speed (t) Fluid retention rate Example 1 46 91.2% Example 2 54 90.1% Example 3 38 92.3% Comparative Example 1 98 87.0% Comparative Example 2 87 88.4% Comparative Example 3 73 89.2%

[0065] As can be seen from Table 2, the liquid absorption and retention capacity of the silicon-carbon composite materials obtained in Examples 1-3 is significantly higher than that of the comparative example, indicating that the silicon-carbon composite materials of the present invention have a higher liquid absorption and retention capacity. The reason may be that the specific surface area of ​​the composite materials in the examples is larger, which improves the liquid absorption and retention capacity of the materials.

[0066] C. Rate and Cycle Performance

[0067] The soft-pack batteries containing the composite materials of Examples 1-3 and Comparative Examples 1-3 were subjected to cycle performance tests and rate tests, and the test conditions were: charge and discharge voltage range of 2.5 to 4.2 V, temperature of 25 ± 3.0 ° C, charge and discharge rate of 1.0 C / 1.0 C, and cycle number of 500 times. Rate test: Test the constant current ratio of the material under 2C conditions, constant current ratio = 2C constant current capacity / (2C constant current capacity + 0.1C constant voltage capacity), and the test results are shown in Table 3.

[0068] Table 3

[0069] Lithium-ion battery Initial capacity retention rate (%) Capacity retention after 500 cycles (%) 2C constant current ratio Example 1 100 95.8 91.2% Example 2 100 96.1 90.5% Example 3 100 94.7 92.5% Comparative Example 1 100 90.8 85.4% Comparative Example 2 100 91.5 84.9% Comparative Example 3 100 92.0 86.2%

[0070] It can be seen from Table 3 that the cycle performance of the soft-pack lithium-ion battery prepared using the silicon-carbon composite material of the present invention is better than that of the comparative example. The reason is that the silicon-carbon composite material of the present invention has lower expansion, porous structure and high specific surface area, which improves the liquid retention of the material and improves the cycle performance; at the same time, the example material has higher powder electronic conductivity, which improves its kinetic performance, thereby improving its constant current ratio during the charge and discharge process, that is, improving its power performance.

[0071] The above is only a preferred embodiment of the present invention. It should be pointed out that although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that several improvements and modifications may be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention and do not deviate from the scope defined by the claims of the present invention.

Claims

1. A pitch-based silicon-carbon composite material, characterized in that: The composite material presents a core-shell structure, wherein the core is metallic lithium and silicon-doped asphalt-based porous carbon, and the outer shell is a silicon dioxide layer and an amorphous carbon layer from the inside to the outside; calculated based on the composite material mass ratio of 100%, the mass ratio of the silicon dioxide layer in the first shell is 0.5-2wt%, and the mass ratio of the amorphous carbon layer in the second shell is 1-5wt%; the silicon-carbon composite material is prepared from asphalt-based porous carbon; The preparation method of the asphalt-based porous carbon is as follows: coal tar pitch, sodium bicarbonate, activator, and sodium borohydride are added to a ball mill according to a mass ratio of coal tar pitch: sodium bicarbonate: activator: sodium borohydride = 100: 1-5: 1-5: 1-5, mixed evenly, and transferred to a tube furnace, first heated to 500-600° C. and kept for 1-6 hours, and then heated to 850-1150° C. and sintered for 1-6 hours to obtain the asphalt-based porous carbon; The activator is one or more of silver chloride, copper chloride and zinc chloride.

2. The method for preparing the asphalt-based silicon-carbon composite material according to claim 1, characterized in that: The steps include: Step S1: adding coal tar pitch, sodium bicarbonate, activator and sodium borohydride to a ball mill according to the mass ratio of coal tar pitch: sodium bicarbonate: activator: sodium borohydride = 100: 1-5: 1-5: 1-5, mixing them evenly, and transferring them to a tube furnace, first heating them to 500-600° C. and keeping them for 1-6 hours, and then heating them to 850-1150° C. and sintering them for 1-6 hours to obtain asphalt-based porous carbon; Step S2: according to the mass ratio of asphalt-based porous carbon: silane liquid: metal compound = 100-200: 100: 10-30, the asphalt-based porous carbon is transferred to the tubular furnace A, the alkyl silane liquid and the metal compound liquid are neutralized and added to the reaction to mix evenly, and the mixture is gasified at a temperature of 400-600° C. under a vacuum degree of 0.1-1 MPa, and then introduced into the tubular furnace A at a flow rate of 100-500 ml / min and an introduction time of 30-300 min to perform silicon and metal co-deposition to obtain a metal-doped silicon-carbon precursor material; Step S3: transferring the metal-doped silicon-carbon precursor material to a tube furnace, then heating it to 100-200° C. and introducing an oxidizing mixed gas for passivation for 1-6 hours, then heating it to 500-800° C. and introducing a carbon source gas for vapor deposition to deposit amorphous carbon and achieve secondary coating to obtain a silicon-carbon composite material; In step S2, the metal compound is selected from one or more of lithium acetate, methyl lithium and butyl lithium.

3. The preparation method according to claim 2, characterized in that: The activator in step S1 is one or more of silver chloride, copper chloride and zinc chloride.

4. The preparation method according to claim 2, characterized in that: In step S2, the silane gas is selected from one or more of dimethylsilane, diethylsilane, dichlorodiethylsilane, methyldichlorosilane, trichlorosilane, monosilane, and disilane.

5. The preparation method according to claim 2, characterized in that: The oxidizing mixed gas in step S3 is a mixed gas of one of oxygen, nitrogen dioxide, carbon monoxide, bromine and oxybromine and argon, with a volume ratio of 1-5:10 and a flow rate of 10-100 SCCM.

6. The preparation method according to claim 2, characterized in that: In step S3, the carbon source gas is selected from one or more of methane, ethane, acetylene, and ethylene, with a flow rate of 10-100 SCCM.

7. A negative electrode plate for a lithium ion battery, characterized in that: The negative electrode plate includes a negative electrode current collector and a negative electrode material coated on at least one surface of the negative electrode current collector, and the negative electrode material includes the asphalt-based silicon-carbon composite material according to claim 1 or the asphalt-based silicon-carbon composite material prepared according to any one of claims 2-6.

8. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet and a separator separated between the positive electrode sheet and the negative electrode sheet, and the negative electrode sheet is the negative electrode sheet of the lithium-ion battery according to claim 7.

Citation Information

Patent Citations

  • Lithium ion capacitor and preparation method thereof

    CN111435632A

  • Silicon-carbon composite negative electrode material and preparation method and application thereof

    CN114068901A

  • Amorphous carbon coated magnesium-lithium alloy doped silicon-carbon composite material and preparation method thereof

    CN117913239A